Antihyperglycaemic and Hepatoprotective Effect of Phyllanthus Emblica Fruit in Diabetic Animal Model - M, Mittal (Journal of Medical Biomedical and Applied Sciences, 2014)
The present study is aimed to evaluate the antihyperglycemic activity of ethanolic extract of Phyllanthus emblica fruits in alloxan in-duced diabetic rats. Whistar rats were made made diabetic with alloxan and ethanolic extract of P.emblica is administred in a dose of 100mg/kg and 150mg/kg body weight for antidiabetic activity. Blood glucose levels were estimated in all groups on 0, 10th, 20th, 30th day of treatment with P.emblica. The cholesterol, triglycerides, AST, ALT, ALP were estimated on 30th day of treatment in all group compared against diabetic control group. The ethanolic extract of fruit of P.emblica 100mg/kg & 150 mg/kg body weight showed dose dependenent reduction in blood glucose level in alloxan induced diabetic rats, cholesterol, triglyceride and other hepatic markers are also reduced when treated with ethanolic extract of P.emblica in alloxan induced diabetic rats.Â